2022
DOI: 10.1186/s13065-022-00828-8
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and bioactivity of ferulic acid derivatives containing an β-amino alcohol

Abstract: Background Plant diseases caused by viruses and bacteria cause huge economic losses due to the lack of effective control agents. New potential pesticides can be discovered through biomimetic synthesis and structural modification of natural products. A series of ferulic acid derivatives containing an β-amino alcohol were designed and synthesized, and their biological activities were evaluated. Result Bioassays results showed that the EC50 values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Taking Chenopodium amaranticolor as the experimental plant, the anti‐CMV activities of the target compounds were tested by the half‐leaf method at 500 μg mL −1 17,19,20 . At the same time, for the compounds with special activities, their activities at 500, 250, 125, 62.5, and 31.25 μg mL −1 were tested, and the half maximal effective concentration (EC 50 ) value was calculated 21 …”
Section: Biological Activity Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking Chenopodium amaranticolor as the experimental plant, the anti‐CMV activities of the target compounds were tested by the half‐leaf method at 500 μg mL −1 17,19,20 . At the same time, for the compounds with special activities, their activities at 500, 250, 125, 62.5, and 31.25 μg mL −1 were tested, and the half maximal effective concentration (EC 50 ) value was calculated 21 …”
Section: Biological Activity Test Methodsmentioning
confidence: 99%
“…Taking Chenopodium amaranticolor as the experimental plant, the anti-CMV activities of the target compounds were tested by the half-leaf method at 500 μg mL −1 . 17,19,20 At the same time, for the compounds with special activities, their activities at 500, 250, 125, 62.5, and 31.25 μg mL −1 were tested, and the half maximal effective concentration (EC 50 ) value was calculated. 21 3.1.1 Curative activity of target compounds against CMV Using plants with the same growth cycle, the carborundum powder was spread evenly on the leaves, the viruses were gently brushed on the leaves with a brush, and after 30 min of virus action, the carborundum powder was washed off with water.…”
Section: In Vivo Anti-cmv Activity Testmentioning
confidence: 99%
“…It has been reported that the biological activity of ferulic acid can be altered by creating its derivatives. A series of such derivatives of ferulic acid with β-amino alcohol has been previously reported ( Figure 1 ) [ 16 ]. The chemical structure of ferulic acid has the presence of benzene rings with a carboxylic group.…”
Section: Sources Chemistry and Structural Activity Relationship Of Fe...mentioning
confidence: 99%
“…5–8 Among them, ferulic acid is a natural plant metabolite that is usually found in Ferula assa-foetida L., Ligusticum chuanxiong Hort., Catalpa ovata G. Don 9 and so on. Ferulic acid is a phenylpropanoid natural product containing a phenolic hydroxyl group and has a great variety of pharmacological activities, such as herbicidal, 10,11 fungicidal, 12,13 antiviral, 14,15 and bactericidal 16–18 activities. Therefore, ferulic acid derivatives are a class of lead compounds designed and synthesized for new pesticides.…”
Section: Introductionmentioning
confidence: 99%